Profile and Analysis of Lightning Victims Brought to MGH, Khammam; Telangana State - Guntheti, Bharath Kumar; Singh , Uday Pal (Journal of Indian Academy of Forensic Medicine, 2015)
When there is discharge of electricity between clouds lightning occurs. This study was aimed to  study the profile and analysis of lightning victims and pattern of injuries. Thirty Eight victims of lightning  fatalities were identified from emergency Dept. of MGH, Dept. of Forensic Medicine, for a period of 3  years. Middle aged males, married, illiterates from rural region, belongs to low socioeconomic group,  Hindu community are the most common victims when working as farmers in the open field afternoon time  on Saturdays with peak incidence in monsoon season. The pattern of injuries is noted as burns over body  in 36 (94.73%) cases with maximum cases having Lichtenberg figures 26 (68.42%), followed by linear  burns 8 (21.05%). Magnetization of the metal worn noted. Maximum cases 34 (89.47%) were brought  dead, post-mortem findings were nonspecific, petechial hemorrhage seen in the brain and the spinal cord.  Cardiopulmonary arrest following lightning was most common in 28 (77.77%) cases. High  incidence of lightning strikes in this region and requires a more systemic and detailed investigative  protocol in lightning related deaths. Such deaths are unpredictable but preventable with better public  education, rural health care.
Keywords: Lightning; Victims; Pattern of injuries; Incidence; death